"An Islamic Atlantic Revolution:" Dan Fodio's Jihād and Slave Rebellion in Bahia and Cuba, 1804-1844. (May 2013) - Barcia, Manuel
Abstract : Over the past decades the impact of Atlantic revolutions on slave revolts in the Americas has become a constant subject of discussion. The ways in which the French and Haitian revolutions determined the actions of African slaves in the Americas has only been matched by the relevance given by scholars to the impact of British abolitionist policies from 1807 onwards. While, at least for a period, a series of events that took place in Europe and the Americas did influence the choices presented to those who fought against enslavement and slavery, for most of the first half of the nineteenth century they were not by any means the only ones, or for that matter the most important historical events behind their acts of resistance. Islam, and in particular, the Fulani Jihād that altered the balance of power in the Western Sudan and, by extension, the parameters of the slave trade in the area, was just as important. Every rebellion led by the Yoruba or the Hausa (and even occasionally by the Mina, Ewe-Fon, and even Igbo) slaves in Bahia and Cuba during the period examined in this paper was, to a certain extent, a consequence of this Jihād. In this article I attempt to establish this connection by looking at African, American, and European primary sources. My key argument is that the lives of those who were sent from these West African regions to the New World as slaves continued to be signaled by their African experience and that their rebel actions were directly or indirectly a consequence of the Fulani Jihād.